(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The main objective of this research is to estimate the effect of imports on employment in food industry in private sector in Syria in the period between (1980-2010) using the Johansen test and vector error correction model (VECM), and we have found that there is a weak negative impact of imports on employment in short-run, but it is significant only at 10% level.